Notes on Heortia vitessoides (Moore)(Lepidoptera: Crambidae: Odontiinae), an economically potential pest of Aquilaria Malaccensis Benth in Malaysia - Ahmad Said Sajap (Pusat Sistematik Serangga ,UKM, 2013)

(untitled)
A lepidopteran moth, Heortia vitessoides (Moore) (Crambidae: Odontiinae) was recorded for the first time attacking saplings of Aquilaria malaccensis Benth (Thymelaeaceae) in several plantations in Malaysia. The larvae have a brown head and pale green body with a broad dotted black line along each side their abdomen. They live gregariously in shelters of leaves that are loosely tied together by silken threads. Their feeding activities could cause severe defoliations on saplings in the field. Even though most of the saplings survived from single infestation but repeated infestations could interfere the growth and development of the tree. Thus recurring infestations could pose a serious economic implication to productivity of the trees.